Concept, etiology, and pathomechanics of hallux rigidus - Monteagudo de la Rosa, Manuel; Viladot-Pericé, Ramón (Journal of the Foot & Ankle, 2021)
There is a continuous anatomical, functional and pathomechanical roadmap from functional hallux limitus to hallux rigidus. Although many etiologies for hallux rigidus have been studied it is very probable that it has a primary origin with less-than-ideal movement when we are born. Upon a restricted range of motion, symptoms may arise depending on the amount of work and how compensatory mechanisms work around the first metatarsophalangeal joint. Changes occurring at the joint that allow the transition from a sliding movement mechanism (physiological) to a rolling mechanism (pathological) may trigger anatomical and functional changes resulting in pain and dysfunction. Any surgical technique that is able to restore the sliding mechanism to the first metatarsophalangeal joint will have a positive impact on pain and function in a patient with a symptomatic functional hallux limitus/rigidus. Level of Evidence V; Therapeutic Study; Expert opinion.